Efficacy and safety of low-dose glucocorticoids combined with methotrexate and hydroxychloroquine in the treatment of early rheumatoid arthritis: A single-center, randomized, double-blind clinical trial. Issue 27 (2nd July 2020) - Hua, Li; Du, Hongwei; Ying, Mingliang; Wu, Honghua; Fan, Jia; Shi, Xiaowei
Abstract: Introduction: Glucocorticoids (GCs), especially low-dose GCs, are commonly prescribed for rheumatoid arthritis (RA), although the risk/benefit ratio is controversial. A randomized, double-blind clinical trial was performed to evaluate the efficacy and safety of low-dose oral GCs combined with methotrexate (MTX) and hydroxychloroquine (HCQ) in early RA (ERA). Methods: Eighty untreated ERA patients were randomized into the trial (GCs + MTX + HCQ) and control (placebo + MTX + HCQ) groups, for 1-year treatment. Therapeutic evaluation indices were American College of Rheumatology (ACR) 20 of ACR, disease activity score (DAS) 28- erythrocyte sedimentation rate (ESR), visual analog scale scores, joint function, health assessment questionnaire-disability index score, morning stiffness duration, C-reaction protein and ESR. The clinical indicators were evaluated pre-treatment and at 1st, 3th, 6th and 12th month of treatment. The MRI data of single joint (ie, the most swollen joint) for each patient were acquired with a revised OMERACT RAMRIS Scoring System before and after treatment. The correlation analysis was adopted to confirm whether the efficacy of GC treatment is related to the time of RA onset. The side effects (eg, gastrointestinal reactions, liver dysfunction, upper respiratory tract infection, leukocyte reduction) were also monitored. Results: At 1st month, 55% and 20% cases in the experimental and control groups achieved ACR20 response, respectively, indicating a significant difference ( χ 2 = 16.157, P < .001). This trend continued until 6th month. At 12th month, the number of patients achieved ACR20 response was similar in both groups. At 1st to 6th month, DAS28- ESR scores in the experimental group were significantly lower than control values (all p < .05). The experimental group showed improved inflammation, quality of life and radiological symptoms. Bone erosion remained unchanged in the experimental group, while worsening in control group. Correlation coefficients between RA duration and DAS28-ESR score were 0.496, 0.464, 0.509, and 0.550 at 1st, 3th, 6th, and 12th month, respectively. No differences were found in adverse events between the 2 groups. Conclusions: Low-dose GCs combined with MTX and HCQ significantly achieves disease remission indexed by ACR20 and DAS28-ESR, and improves clinical and radiological outcomes in ERA patients at the early stage, with superiority over placebo + MTX + HCQ, without enhancing adverse reactions.